Prevalence and associated factors of myopia in children and adolescents in Russia: the Ural Children Eye Study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Iakupova, Ellina M.; Panda-Jonas, Songhomitra; Gilemzianova, Leisan I.; Garipova, Liana A.; Khakimov, Dinar A.; Islamova, Liaisan I.; Jonas, Jost B. (British journal of ophthalmology, 2024)
Background To assess the prevalence of myopia and the distribution of ocular axial length as surrogate for myopic refractive error in school children in a population in Russia. - Methods The Ural Children Eye Study, a school-based case-control study, was conducted in Ufa/Bashkortostan/Russia from 2019 to 2022 and included 4933 children (age: 9.7±2.6 years; range: 6.2-18.8 years). The parents underwent a detailed interview and the children an ophthalmological and general examination. - Results Prevalence of any myopia (≤−0.50 dioptres (D)), minor myopia (−0.50 D to −1.0 D), moderate myopia (−1.01 D to −5.99 D) and high myopia (≤−6.0D) was 2187/3737 (46.2%; 95% CI 44.8% to 48.6%), 693/4737 (14.6%; 95% CI 13.6% to 15.6%), 1430/4737 (30.2%; 95% CI 28.9% to 31.5%) and 64/4737 (1.4%; 95% CI 1.0% to 1.7%), respectively. In the children aged 17+ years, prevalence of any, minor, moderate and high myopia was 170/259 (65.6%; 95% CI 59.8% to 71.5%), 130/259 (50.2%; 95% CI 44.1% to 56.3%), 28/259 (10.8%; 95% CI 7.0% to 14.6%) and 12/259 (4.6%; 95% CI 2.1% to 7.2%), respectively. After adjusting for corneal refractive power (beta: 0.09) and lens thickness (beta: −0.08), larger myopic refractive error was associated (r2=0.19) with older age (beta: 0.33), female sex (beta: 0.04), higher prevalence of maternal (beta: 0.15) and paternal (beta: 0.12) myopia, more time spent in school, with reading books or playing with the cell phone (beta: 0.05) and less total time spent outdoors (beta: 0.05). Axial length and myopic refractive error increased by 0.12 mm (95% CI 0.11 to 0.13) and −0.18 D (95% CI 0.17 to 0.20), respectively, per year of age. - Conclusions In this ethnically mixed urban school children population from Russia, prevalence of any myopia (65.6%) and high myopia (4.6%) in children aged 17+ years was higher than in adult populations in the same region and it was lower than in East Asian school children, with similar associated factors.
Online veröffentlicht: 5. April 2023
Zu diesem Artikel gibt es Supplementary Material (7 Seiten)
Gesehen am 15.02.2024